Relationship between body length and the length of other body parts of Pterigoplihchtys pardalis from the Air Hitam and Siak Rivers Riau - Dechy Puspita Sari; Deni Efizon; Chaidir P. Pulungan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Pterigoplihchtys pardalis is originated from South America, but it has been distributed evenly in many rivers in Indonesia. Information on length-length relationship is important for conducting research related to biological aspects and conservation of this fish. However, this information is rare. To get information on length-length relationship, a study has been conducted from February to May 2015. The fish was sampled from the Air Hitam River (St 1) and the Siak River (St 2). Totally 121 fish from the Air Hitam River and 112 fishes from the Siak River were used in this study. Body parts measured were the standard length and other characteristics such as the length, widht and height of the head; body height and peduncle’s length. Results shown that the relationship between body length and other body parts (r) is 0,918 – 0,986 for Air Hitam River and r = 0.889 – 0,992 for Siak River. It’s indicate that there is very significant relationship between body length and the length of other body parts.Key words: Pterigoplihchtys pardalis, length-length relationship, Air Hitam River , Siak River